2018
DOI: 10.3390/pr6090172
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Permeation through Mixed-Matrix Membranes: A Review

Abstract: Over the past three decades, mixed-matrix membranes (MMMs), comprising an inorganic filler phase embedded in a polymer matrix, have emerged as a promising alternative to overcome limitations of conventional polymer and inorganic membranes. However, while much effort has been devoted to MMMs in practice, their modeling is largely based on early theories for transport in composites. These theories consider uniform transport properties and driving force, and thus models for the permeability in MMMs often perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 188 publications
(667 reference statements)
4
60
0
Order By: Relevance
“…In the proposed model, for precise evaluation of the gas transport through MMMs, the effective diffusion coefficient is utilized . In this mechanism, the transport of permeate gas molecules included dissolving (adsorb) the feed side, diffusing across the membrane, and then releasing (desorb) to the permeate side …”
Section: Methodsmentioning
confidence: 99%
“…In the proposed model, for precise evaluation of the gas transport through MMMs, the effective diffusion coefficient is utilized . In this mechanism, the transport of permeate gas molecules included dissolving (adsorb) the feed side, diffusing across the membrane, and then releasing (desorb) to the permeate side …”
Section: Methodsmentioning
confidence: 99%
“…However, the numerical solution of coupled partial differential equations requires advanced methods such as the finite-element, finite difference or boundary volume methods and this limits the practical use of the method in predicting the permeabilities. Studies implementing simulation-based rigorous modeling approach can be found in a recent review [78]. The models listed in Tables 1 and 2 are used to predict the permeability in MMMs by using the experimentally measured permeabilities of filler and continuous phases.…”
Section: Fundamental Approaches For Predicting Permeation Through Mmmsmentioning
confidence: 99%
“…Comparison of experimental and theoretical (a) O 2 (b) N 2 permeabilities predicted from different effective medium theory based models for CMS/Ultem MMM. Adapted from Ref [78]…”
mentioning
confidence: 99%
“…Recently, there has been a strong trend to reduce the particle size to improve the surface quality of the final coatings and lead to the considerable cost savings of material and energy [2][3][4][5][6][7]. Therefore, ultrafine powder coatings (D 50 < 25 µm) have attracted more and more attention from the finishing industries, such as oral drug delivery systems, dental and orthopedic implants and the pharmaceutical industry [8][9][10].…”
Section: Introductionmentioning
confidence: 99%